Sleep Disorders and Stroke Rehabilitation: Exploration of Treatment Strategies from the Neuroplasticity Perspective - WU Xiaoli, LIU Lixu (Zhongguo cuzhong zazhi)
Abstract: Stroke, as a neurological disease characterized by high disability and mortality rates, poses a significant threat to the long-term quality of life for patients. Effective neurofunctional rehabilitation measures can substantially mitigate the long-term disabilities induced by stroke. Motor relearning, a crucial mechanism in post-stroke rehabilitation, is heavily reliant on good sleep quality. However, stroke patients often suffer from sleep disorders, which have a non-negligible negative impact on rehabilitation outcomes. This paper delved into the bidirectional relationship and pathophysiological mechanisms between sleep disorders and stroke rehabilitation. It also reviewed the application and prospect of emerging technologies such as non-invasive/invasive brain stimulation, virtual reality therapy, wearable sleep tracking devices, and gene therapy in stroke patients with sleep disorders, aiming to provide new perspectives and effective methods for optimizing stroke rehabilitation strategies, so as to enhance the rehabilitation effects and quality of life for stroke patients.